Penerapan Model Pembelajaran Think Pair Share (Tps) Dalam Meingkatkan Hasil Belajar Matemtika Siswa Kelas IV SD Negeri 14 Biru Kecamatan Tanete Riattang Kabupaten Bone - Mei Wulangdari; Awaluddin Muin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
. This study aims to improve the learning outcomes of mathematics through Think Pair Share (TPS) learning model in fourth grade students of SD Negeri 14 Biru Tanete Riattang Sub-district  Bone District. Students' learning outcomes on material count arithmetic addition and fractional breaking is still much below the established KKM that is 75. This is caused by factors derived from the teacher are: (1) the presentation of the material is still monotonous, (2) the lack of mastery of the class, (3) The teacher's attention to the students is less, that is only focused on some students only, (4) instructional Media. Meanwhile, from the aspect of the students, it can be seen that during the learning process of mathematics, (1) the students feel bored during the learning process, (2) the students become noisy, (3) other students are allowed to do whatever activities they want, (4) teach. Therefore researchers attempt to solve problems through the application of Think Pair Share (TPS) learning model. This type of research is a classroom action research (PTK) consisting of planning, implementation, observation and reflection. The focus of the research is the application of Think Pair Share (TPS) learning model and student learning outcomes in mathematics learning. Subjects in this study were active fourth graders and enrolled in the even semester of the academic year 2016/2017 consisting of 24 students, 11 male students and 13 female students. Technique of collecting data in this research is done obeservasi, tes and documentation. While data analysis technique in this research that is 1) reducing data, 2) data presentation and 3) drawing conclusion. The results of the research have been analyzed, indicating that there is an increase in student learning outcomes from cycle I with enough category (C) increased to either category (B) on the second cycle. Results of data analysis concluded that the model of Think Pair Share (TPS) can improve student learning outcomes in learning mathematics in class IV SD Negeri 14 Biru Tanete Riattang sub-district Bone District.